Medea's daughters: forming and performing the woman who kills - Jones, Jennifer (Ohio State University Press, 2003)
Female offenders and offensive females -- Petty (t)reasons for killing her lord and master -- Absence of (m)alice on the Victorian stage -- A jury of her peers -- Totaled women: the battered wife defense -- Medea returns -- Narratives of resistance.